A laboratory information management system for the analysis of tritium (3H) in environmental waters. (July 2018) - Belachew, Dagnachew Legesse; Terzer-Wassmuth, Stefan; Wassenaar, Leonard I.; Klaus, Philipp M.; Copia, Lorenzo; Araguás, Luis J. Araguás; Aggarwal, Pradeep
Abstract: Accurate and precise measurements of low levels of tritium ( 3 H) in environmental waters are difficult to attain due to complex steps of sample preparation, electrolytic enrichment, liquid scintillation decay counting, and extensive data processing. We present a Microsoft Access™ relational database application, TRIMS (Tritium Information Management System) to assist with sample and data processing of tritium analysis by managing the processes from sample registration and analysis to reporting and archiving. A complete uncertainty propagation algorithm ensures tritium results are reported with robust uncertainty metrics. TRIMS will help to increase laboratory productivity and improve the accuracy and precision of 3 H assays. The software supports several enrichment protocols and LSC counter types. TRIMS is available for download at no cost from the IAEA atwww.iaea.org/water . Highlights: Low-level tritium analysis in environmental waters involves electrolytic enrichment and decay counting. Accurate and precise measurements of low levels of tritium ( 3 H) in environmental waters are important for groundwater dating. Most tritium laboratories have difficulties in properly computing uncertainty. Identical treatment (standardized approach) is required for local, regional to global inter-comparison.